Karyotype Analysis and Genome Size Estimation Using Flow Cytometry of the Genus Encyclia Hook. (Orchidaceae: Laeliinae) - Chengcheng Zhou; Qingyun Leng; Jinping Lu; Shisong Xu; Donghui Peng; Junmei Yin; Junhai Niu (Diversity)
Encyclia Hook. is a tropical orchid known for its delightful fragrance and distinctive flower shapes, which have been widely used as superior parents for inter and intrageneric breeding. In this study, karyotype analysis shows that the number of chromosomes in diploid plants of Encyclia is 40, with all species exhibiting mesial and central filamentous chromosomes. The karyotype of diploid plants is primarily 2B. Among the three detected intergeneric hybrids, both Enanthleya Circus Lady ‘Coastal Star’ and Guaricyclia Kyoguchi ‘Fumi’ are triploid, while Robertsara ‘Green Wonder’ is tetraploid. By evaluating various lysates and tissues, a flow cytometry system (FCM) is developed with Galbraith’s buffer (GLB) and tender leaves. By using Dendrobium officinale as an external reference, the genome size of the Encyclia species and its intra and intergeneric hybrids are assessed, which ranges from 1.07 Gb to 3.23 Gb. These results will establish a foundation for high-throughput identification of germplasms, advance crossbreeding efforts, and enhance the understanding of the genome in Encyclia.